Morphological Features Growth and Development of Dendrobium sp. Orchid as Influenced by Nutrient Spray (Journal of Environmental Science and Natural Resources, 2012)
The experiment was conducted to see the effect of nutrient spray on morphophysiological feature and growth of three orchid varieties namely Dendrobium Red Bull, D. Kasim Gold and D White 5 N. Results revealed that the morphophysiological and growth attributes significantly varied among the cultivars. D Red Bull showed the highest plant height, leaf length, leaf area and stem diameter among the varieties. D. White 5 N was superior in leaf number and total leaf area and D. Kasim Gold was superior in leaf area index and leaf width to the other varieties. On the other hand, the trend of increasing in leaf length, leaf width, leaf area index, leaf number, leaf area and total leaf area was the highest for N:P:K as 10:25:30. Plant height and stem diameter was maximum for N:P:K as 15:20:20. In conclusion, low level of nitrogen and high level of phosphorus and potassium was suitable for leaf length, leaf width, leaf area index, leaf number, leaf area and total leaf area while high level of nitrogen and low level of potassium was suitable for plant height and stem diameter. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11598 J. Environ. Sci. & Natural Resources, 5(1): 309-318, 2012